2020
DOI: 10.1097/md.0000000000020631
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of probiotics for the treatment of children with antibiotic-associated diarrhea

Abstract: This retrospective study aimed to explore the benefits and safety of probiotics (live combined Bacillus subtilis and Enterococcus faecium granules with multivitamines) for the treatment of children with antibiotic-associated diarrhea (AAD). A total of 72 children with AAD were analyzed in this study. Of these, 36 children received routine treatment plus probiotics, and were assigned to a treatment group. The other 36 children underwent routine treatment alone, and were assigned to a control group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Multispecies probiotics [Lactobacillus acidophilus (McFarland et al, 2018;Łukasik and Szajewska, 2018), Bacillus subtilis (Rui and Ma, 2020), Saccharomyces cerevisiae (Thévenot et al, 2015)] have achieved certain results in human application, and there are similar reports in animals. Studies have found that Lactobacillus acidophilus (Sharma et al, 2018), Bacillus subtilis (Sun et al, 2010;Zhang et al, 2017;Wood et al, 2019), and Saccharomyces cerevisiae (Fomenky et al, 2018;Villot et al, 2019) can improve calf growth performance by improving immune function and balancing the structure of intestinal microbiota.…”
Section: Introductionmentioning
confidence: 90%
“…Multispecies probiotics [Lactobacillus acidophilus (McFarland et al, 2018;Łukasik and Szajewska, 2018), Bacillus subtilis (Rui and Ma, 2020), Saccharomyces cerevisiae (Thévenot et al, 2015)] have achieved certain results in human application, and there are similar reports in animals. Studies have found that Lactobacillus acidophilus (Sharma et al, 2018), Bacillus subtilis (Sun et al, 2010;Zhang et al, 2017;Wood et al, 2019), and Saccharomyces cerevisiae (Fomenky et al, 2018;Villot et al, 2019) can improve calf growth performance by improving immune function and balancing the structure of intestinal microbiota.…”
Section: Introductionmentioning
confidence: 90%
“…It is estimated that from 11 to 30% of children treated with antibiotics (mainly β-lactam ones and vancomycin) suffer from intestinal discomfort and diarrheas [11][12][13]. Diarrhea is especially dangerous for small children/toddlers as it may cause malfunction of the water-electrolyte balance of their bodies within a short period of time [14].…”
Section: Introductionmentioning
confidence: 99%